Gold-catalysis: reactions of organogold compounds with electrophiles - Hashmi, A. Stephen K.; Dondeti Ramamurthi, Tanuja; Todd, Matthew H.; Tsang, Althea S.-K.; Graf, Katharina (Australian journal of chemistry, 2010)
Different arylgold(i), one alkynylgold(i), and one vinylgold(i) triphenylphosphane complexes were subjected to electrophilic halogenation reagents. With N-chlorosuccinimid, N-bromosuccinimid, and N-iodosuccinimid as well as the Barluenga reagent, selectively halogenated compounds were obtained. Trifluoroacetic acid, as a source of protons, leads to a clean protodeauration. With N-fluorobenzenesulfonimide or Selectfluor, exclusively a homocoupling was observed. For the precursor of the vinylgold(i) complex, a similar oxidative coupling could be induced by gold(iii) chloride. Reactions with silicon or tin electrophiles failed.
Gesehen am 27.03.2023